Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue of the ileum in an adult presenting with intussusception: a case report and literature review - Da, Binlin; Zhang, Juanjuan; Zhu, Feng; Wang, Zhiming; Diao, Yanqing (Frontiers in Oncology, 2024)
Extranodal marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue (EMZL), also known as MALT lymphoma, is an extra-nodal multiorgan-invasive proliferative lymphoma composed of small B cells with variable morphology. It most commonly occurs in the digestive tract, with a high prevalence in the stomach, but EMZL originating in the small intestine are rare and lack specificity of clinical manifestations, which makes it easy to be misdiagnosed. Herein, we report a rare case of small intestinal EMZL presentation as intussusception in a 32-year-old man. A colonoscopy performed at the local hospital revealed a pedicled polyp about 5*5 cm in size with a rough surface and hyperemia was seen in the ileocecal region. He was admitted to our hospital for polypectomy. A contrastenhanced computed tomographic (CT) scan suggested ileocolic intussusception which was subsequently confirmed by a colonoscopy in our hospital. Adult intussusception is relatively rare, with 90% of cases having a known causative mechanism and of 40% of cases caused by primary or secondary malignancies. Therefore, we performed laparoscopic-assisted right hemicolectomy for the patient. The resected specimen showed that the terminal ileum intussuscepted into the ascending colon and the intussusception was hyperemia and edema, and a 2.5 x 2.5 x 1.5 cm mass was seen at the end of the intussusception. Postoperative pathology revealed the mass was EMZL, partially transformed to large B-cell lymphoma. Then the patient was transferred to the hematology department and completed PET-CT showing postoperative manifestations of primary intestinal lymphoma, Lugano staging IE2. Although EMZL was an indolent lymphoma and the patient was in the early stage, the rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) regimen was given in view of the histological transformation. The patient is ongoing follow-up. This was a rare case of small intestinal mass due to EMZL presented as intussusception in adult, which highlighted laparoscopic-assisted enterectomy as a potential therapeutic approach in the multidisciplinary collaborative therapy of small intestine EMZL.